Design of an axially concave pad profile for a large turbine tilting-pad bearing. (April 2017) - Kukla, Sebastian; Buchhorn, Nico; Bender, Beate
To improve operational safety and/or achieve a higher load capacity of turbine tilting-pad bearings, an axially concave pad profile is presented. The thermal and mechanical stress of the loaded pads of a test bearing in load between pivot configuration has been analysed. Both film thickness and pressure distribution have been measured at a very high resolution. A fluid film calculation program in combination with a finite-volume-based structural mechanics program is used to simulate the deformation of a single pad under high circumferential speeds. In this context, the axial and tangential heat transfer coefficients of the pad surface, which act as boundary conditions for the calculation of the 3D temperature distribution, are determined using an optimization process. Herein, the match of predicted and measured pad temperatures is the goal. It can be shown that there must be a huge difference in heat transfer in axial and tangential direction in order to match the large measured temperature gradient in circumferential direction. Based on the measured deformed profile the program code is used to derive a concave pad profile, which will result in an axially non-arched sliding surface under the expected thermal load. Therefore, an iterative simulation procedure is used. By decreasing the axial arching of the pad and thus the large film thickness at the axial ends using an improved profile designed for a specific operation point, the minimum film thickness and maximum pad temperature can be influenced beneficially. The comparison of measurement data and calculation results shows very good agreement regarding the pad deformations. The results indicate that by axially concave profiling of the loaded pads of a large tilting-pad bearing for a specific operation point, the static characteristics in the form of temperature, film thickness and load capacity can be improved.